Estimation of Carbon Reserves Above Soil Surface in Agroforestry Patterns in Mount Sasak, West Lombok District - Antareja, Gde Margin; Wahyuningsih, Endah; Valentino, Niechi (Jurnal Biologi Tropis, 2024)
The increase in greenhouse gases will affect the level of global warming, which is one of the factors causing climate change. The greenhouse gas that has the biggest impact on increasing Earth's temperature is carbon dioxide (CO2). The method for taking sample plots applied in this research is the systematic sampling method with random start, which is point processing which is carried out in a varied or random manner at the start of data collection and then systematically with the distance between plots being balanced. Determining the number of sampling plots refers to the National Forest Inventory (IHN) which states that the minimum limit accepted for sampling intensity is 1%. Therefore, the use of higher sampling in a study will increase the level of accuracy. The reason why candlenuts have a high biomass value is because the average diameter is larger than other types, namely more larger than 35 cm and if the density of Candlenut has a high value this will affect the biomass value to be even higher. This is in accordance with, It is said that tree biomass is calculated using the allometric equation. The carbon value and biomass value of trees will weaken closely, the greater the biomass value, the higher the carbon value. This is due to the stipulated value of 47% carbon content and organic material which is the reason behind this. Based on research findings regarding estimates of above-ground carbon reserves on Mount Sasak, West Lombok Regency, there are carbon reserves of 21,954 tonnes/ha and overall biomass of 46,719 tonnes/ha.